Anno, M. (2021). "Los viajes. Europa". Traductor: Gabriel Álvarez Martínez, Kalandraka. 64pp. - José Antonio Escrig Aparicio (Universidad de Zaragoza, 2022)
MITSUMASA ANNO: JUEGO E IDILIO Reseña de José Antonio Escrig Aparicio,  Anno, M. (2021). "Los viajes. Europa". Traductor: Gabriel Álvarez Martínez, Kalandraka. 64pp